A tripodal heptadentate Schiff base as an active ligand for atom transfer radical polymerization. Issue 39 (16th September 2020) - Xu, Xiaoling; Bao, Chunyang; Hong, Mei; Li, Die; Zhang, Qiang
Abstract : The use of a tripodal heptadentate Schiff base, tris[ N -(2-pyridylmethyl)-2-iminoethyl]amine (Py3 Tren), as an active ligand for atom transfer radical polymerization (ATRP) is reported. Abstract : The use of a tripodal heptadentate Schiff base, tris[ N -(2-pyridylmethyl)-2-iminoethyl]amine (Py3 Tren), as an active ligand for atom transfer radical polymerization (ATRP) is reported. The coordination between Py3 Tren and CuBr2 in solution is investigated by electrospray ionization mass spectrometry, which reveals the generation of a tripod claw-shaped complex by using equimolar quantities of CuBr2 and Py3 Tren. Electrochemical studies of CuBr2 /Py3 Tren complexes demonstrate more negative redox potentials and higher activities compared with those of bidentate CuBr2 / N -ethyl-2-pyridylmethanimine (PyEthyl) complexes. Subsequently, CuBr/Py3 Tren is employed as a catalyst for the normal ATRP of methyl methacrylate (MMA). Well-defined poly(MMA) with controlled molecular weight and narrow polydispersity could be synthesized with high conversions and fast rates even at ambient temperature (30 °C). Activators regenerated by electron transfer (ARGET) ATRP and supplemental activators and reducing agents (SARA) ATRP of acrylate monomers using Py3 Tren as the ligand are also performed to reduce the amounts of metal catalysts for polymerizations.